Knowledge, Attitude and Practice of Dental Students in Tehran regarding Hepatitis B, Hepatitis C, and HIV/AIDS - Karimi, Mandana; Attaran, Nona; Raeesi, Pooya; Ghorbani, Zahra (Journal of Dental School, 2020)
Objectives Healthcare workers including dentists and dental students are at risk of transmission of blood-borne pathogens. Thus, it is imperative to assess their knowledge, attitude and practice regarding the infection control protocols. Methods This cross-sectional study evaluated 164 dental students of Shahid Beheshti University using a self-administered questionnaire. The questionnaire consisted of socio-demographic, knowledge (n=15), attitude (n=27) and performance (n=8) questions regarding hepatitis B, hepatitis C and HIV/AIDS. Data were collected and analyzed using the Kruskal-Wallis and Mann-Whitney U test. Results The mean score of knowledge, attitude and practice regarding hepatitis B, hepatitis C and HIV/AIDS was 18.66 (out of 30), 31.59 (out of 54) and 6.29 (out of 8), respectively. The students had low knowledge level about the routes of transmission, the standard infection control protocols, and infection treatment. They also had poor attitude towards treating the infected patients. There was no significant difference in knowledge, attitude and practice between different academic grades of dental students or males and females. Conclusion The findings did not show satisfactory level of knowledge or attitude of Shahid Beheshti dental students regarding hepatitis B, hepatitis C and HIV/AIDS infections. Thus, more educational programs emphasizing on blood-borne infections are recommended.